EVALUASI KEMAMPUAN DAN PENGHITUNGAN PERINGKAT SISWA MENGGUNAKAN METODE TOPSIS DAN ENTROPY - Muhammad Ghalih; Siti Rohanah (Idaarah: Jurnal Manajemen Pendidikan, 2018)
Abstract: In this study uses techniques for order preference by similarity to ideal solution (TOPSIS) combined within formation Entropy weight to examine the performance of 5 best students. Calculations in teaching and research and improvement ability reveal the short-term and long-term performance. Exact values and intervals characterize the attribute values in the current model. A comparison and experimental analysis show the applicability, feasibility, effectiveness, and advantages of the proposed method. In this study focus on the TOPSIS and Entropy to calculate the student's performance. First, in this study the rationality of TOPSIS conferring to the standard decision theory. It forms that TOPSIS also has a built-in multi-attribute value meaning that not revealed explicitly. To this point, this has been a unknown feature of TOPSIS. Second, Entropy applied for the decision maker's (DM) behavioral propensity into TOPSIS. Finally, to advance evaluation accuracy of student performance, TOPSIS and Entropy applied to ranking the student with several criteria such as Presence (C1), Assignment (C2), Attitude (C3), Midterm-Exam (C4), and Final Exam (C5).